Actions of the soy phytoestrogen genistein in models of human chronic disease: potential involvement of transforming growth factor β. (May 2001) - Kim, H.; Xu, J.; Su, Y.; Xia, H.; Li, L.; Peterson, P.; Murphy-Ullrich, J.; Barnes, S.
Abstract : The structural similarity, but non-identity, between 17β-oestradiol and the soy phytoestrogen genistein suggests that the two compounds will have actions that may be identical in some target biological systems, but different in others. Epidermal growth factor (EGF)-stimulated proliferation of human mammary epithelial cells (that do not express the oestrogen receptor) was significantly suppressed at genistein concentrations (5–10μM) that are attainable physiologically. Others have shown previously that transforming growth factor β (TGFβ) has similar growth-inhibitory effects on human cells. Analysis of the conditioned medium of human mammary epithelial cells exposed to genistein plus EGF showed increased levels of TGFβ relative to those in the medium of cells exposed to EGF or genistein alone. Related experiments in a primate model of menopause demonstrated that ingestion of soy containing isoflavones was correlated with the suppression of neurodegeneration-relevant phosphorylation of the microtubule-associated protein tau, while intake of Premarin (a hormone replacement therapy that is commonly prescribed for women) was not correlated. The results discussed here indicate that genistein, and probably other related phytoestrogens, have pleiotropic actions, some of which may involve TGFβ activity.